Entrepreneurship in the United States and Germany: Attaining the promise of innovation - David B. Audretsch (EconPol Forum, 2024)
If innovation is necessary to tackle the huge economic, political, and social challenges facing society, then entrepreneurship is needed to drive innovation. Both Germany and the US are not only among the most innovative, but also among the most entrepreneurially active countries in the world. Entrepreneurship in Germany and the US has both its strengths and its challenges. The entrepreneurial challenge in Germany is to strengthen and maintain the traditional strengths of incremental innovative entrepreneurship, while building on the impressive transformative entrepreneurship that is taking root in large cities. In contrast, the entrepreneurial challenge for the US is to continue to drive its radical and disruptive innovative entrepreneurship, while expanding the spread of entrepreneurship to less densely populated and more rural regions.
Keywords: 330